Modelos Estadísticos Paramétricos y No Paramétricos para dos Muestras. - Guillen, A.; Badii, M. H.; Abreu, J. L.; Rodríguez, H. (Revista Daena: International Journal of Good Conscience, 2013)
Contingency table and Kolmogorov-Smirnov models both in nominal scale, mann-Whitney model in ordinal scale, and t student model in ratio scale are analyzed and real case examples are given for each model. The procedural steps for the analysis and the interpretation of each and all three models are provided in detailed form.